Treatment Interruption and Regimen Change in Firstgeneration versus Second-generation Tyrosine Kinase Inhibitors used as First-line Therapy for Chronic Myeloid Leukemia - Melea A. Ward; Gang Fang; Kristy L. Richards; Christine M. Walko; Stephanie R. Earnshaw; Laura E. Happe; Susan J. Blalock (Journal of Health Economics and Outcomes Research)
**Background:** Research has shown that treatment interruptions are associated with worse failure-free survival in chronic myeloid leukemia (CML); however they are commonly used in clinical trials to manage adverse events.